Variasi Nilai Peak Ground Acceleration di Kecamatan Prambanan, Kabupaten Klaten - Adelia Saras Nugraheni (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
The Special Region of Yogyakarta (DIY) is characterized by high seismic activity due to its proximity to the subduction zone and the presence of active fault systems, particularly the Opak Fault. The 2006 Yogyakarta earthquake revealed significant vulnerability in local building structures and highlighted the complex geological conditions governing seismic wave propagation. This study aims to calculate and map the Peak Ground Acceleration (PGA) distribution in Prambanan District, Klaten Regency—one of the areas closest to the 2006 earthquake source. PGA values were estimated using the McGuire attenuation relationship, based on a moment magnitude of Mw 6.3 and the hypocentral distance to 88 observation points distributed at approximately 900-meter intervals. The resulting PGA map indicates values ranging from 26.7 to 31.7 gal, with a clear spatial trend showing increasing intensity from the northern to the southern parts of the study area. Higher PGA values occur in regions near the Opak Fault and in areas dominated by unconsolidated volcanic deposits of the young Merapi formation. These loose sediments amplify seismic waves, resulting in stronger ground motion compared to areas composed of more compact sedimentary rocks. The spatial pattern of PGA corresponds well with the distribution of structural damage recorded during the 2006 earthquake. The findings emphasize the significant role of local geology and fault proximity in shaping seismic hazard levels. Consequently, this study provides essential insights for disaster mitigation strategies, land-use planning, and structural vulnerability assessment within the Prambanan area.